2020
DOI: 10.15420/aer.2020.24
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Micro-, Mini- and Multi-Electrode Mapping on Ventricular Substrate Characterisation

Abstract: Accurate substrate characterisation may improve the evolving understanding and treatment of cardiac arrhythmias. During substrate-based ablation techniques, wide practice variations exist with mapping via dedicated multi-electrode catheter or conventional ablation catheters. Recently, newer ablation catheter technology with embedded mapping electrodes have been introduced. This article focuses on the general misconceptions of voltage mapping and more specific differences in unipolar and bipolar signal morpholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 40 publications
0
20
0
Order By: Relevance
“…One could also speculate that under rare circumstances, the ME may miss the surviving bundle by a couple of millimeters while the larger detection from CBE records it. 16 This is strongly suggested by the result of RFCA described in Figure 3B, in which LAVA detected by ME disappeared while LAVA detected by CBE persisted. Another explanation might be that the larger electrodes may have a larger field of view in deeper substrates.…”
Section: Missed Lavas By Microelectrodesmentioning
confidence: 64%
See 1 more Smart Citation
“…One could also speculate that under rare circumstances, the ME may miss the surviving bundle by a couple of millimeters while the larger detection from CBE records it. 16 This is strongly suggested by the result of RFCA described in Figure 3B, in which LAVA detected by ME disappeared while LAVA detected by CBE persisted. Another explanation might be that the larger electrodes may have a larger field of view in deeper substrates.…”
Section: Missed Lavas By Microelectrodesmentioning
confidence: 64%
“…Theoretically, the opposite phenomenon, Type 3 detection, could occur. However, few papers have described this phenomenon in scar-related VT. 15,16 This study showed that 9.2% of LAVAs were detected by CBE without detecting the corresponding signals on ME.…”
Section: Missed Lavas By Microelectrodesmentioning
confidence: 82%
“…All recorded voltages are subject to the size, spacing, and orientation of the recording electrodes relative to the wavefront. 14 The Advisor HD Grid consists of 4 parallel splines that are equally spaced 3 mm apart, each with 4 1-mm electrodes spaced 3 mm apart (4 × 4 electrode configuration). The catheter design allows for the simultaneous recording of bipolar electrograms in the orthogonal direction and within the same dimension.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, the definition of a normal left ventricular endocardial voltage in patients with postinfarct scar is still lacking (169). The values of bipolar electrogram cutoffs are also limited by activation wavefront direction (170), and there are significant voltage differences between diagonally orthogonal bipolar electrode pairs at any given recording site (171). High-density multi-electrode grid catheters can offer improvement because they enable simultaneous recordings from multiple orthogonal directions with the ability to select the largest voltage level in a small region (170,172) and can improve depiction of the diastolic pathway (173).…”
Section: Current Technology For Mapping and Ablation Of Circuit Morphologiesmentioning
confidence: 99%
“…The values of bipolar electrogram cutoffs are also limited by activation wavefront direction (170), and there are significant voltage differences between diagonally orthogonal bipolar electrode pairs at any given recording site (171). High-density multi-electrode grid catheters can offer improvement because they enable simultaneous recordings from multiple orthogonal directions with the ability to select the largest voltage level in a small region (170,172) and can improve depiction of the diastolic pathway (173). Extensive substrate ablation of local abnormal ventricular activity (LAVA) evident during sinus rhythm or pacing is also utilized in targeting (164,174).…”
Section: Current Technology For Mapping and Ablation Of Circuit Morphologiesmentioning
confidence: 99%